Decoupling of wages from productivity: macro-level facts - Schwellnuss, Cyrille; Kappeler, Andreas; Pionnier, Pierre-Alain (Paris, 2017)
"Over the past two decades, aggregate labour productivity growth in most OECD countries has decoupled from real median compensation growth, implying that raising productivity is no longer sufficient to raise real wages for the typical worker. This paper provides a quantitative description of decoupling in OECD countries over the past two decades, with the results suggesting that it is explained by declines in both labour shares and the ratio of median to average wages (a partial measure of wage inequality). Labour shares have declined in about two thirds of the OECD countries covered by the analysis. However, the contribution of labour shares to decoupling is smaller if sectors are excluded for which labour shares are driven by changes in commodity and asset prices or for which labour shares are driven by imputation choices (primary, housing and non-market sectors). The ratio of median to average wages has declined in all but two of the OECD countries covered by the analysis and appears to reflect disproportionate wage growth at the very top of the wage distribution rather than stagnating median wages. The causes for these developments will be analysed in follow-up research."